Genome-wide analysis of NBS-LRR genes revealed contribution of disease resistance from Saccharum spontaneum to modern sugarcane cultivar - Jiang, Zhengjie; Zhao, Mengyu; Qin, Hongzhen; Li, Sicheng; Yang, Xiping (Frontiers in Plant Science, 2023)
During plant evolution, nucleotide-binding sites (NBS) and leucine-rich repeat (LRR) genes have made significant contributions to plant disease resistance. With many high-quality plant genomes sequenced, identification and comprehensive analyses of NBS-LRR genes at whole genome level are of great importance to understand and utilize them. Here, we identified NBS-LRR genes in 23 representative species, and comparisons between species indicated that the number of NBS-LRR genes did not correlate with their genome size, and total number of genes. Collinearity analysis of NBS-LRR genes among four monocotyledonous grass species, including Saccharum spontaneum, Saccharum officinarum, Sorghum bicolor and Miscanthus sinensis, suggested that whole genome duplication may be the major force to affect the number of NBS-LRR genes in sugarcane. Comparisons showed that TNL and CNL had different evolutionary patterns. The results of Ka/Ks ratio of conserved NBS-LRR genes indicated a progressive trend of positive selection on NBS-LRR genes. Transcriptomic analysis of sugarcane challenged by different diseases showed that more differentially expressed NBS-LRR genes were derived from S. spontaneum than from S. officinarum in modern sugarcane cultivars, and the proportion was significantly higher than the expected, revealing the contribution of disease resistance from S. spontaneum. In addition, we observed allele-specific expression of seven NBS-LRR genes under leaf scald, and 125 NBS-LRR genes responding to multiple diseases were identified. Finally, we built a plant NBS-LRR gene database to facilitate subsequent analysis and use of NBS-LRR genes obtained here. In conclusion, this study complemented and completed the research of plant NBS-LRR genes, and discussed how NBS-LRR genes responding to sugarcane diseases, which provided a guide and genetic resources for further research and utilization of NBS-LRR genes.